Lignans from Phyllanthus niruri L. and Their Antifusarium Properties - Neneng Windayani; Yaya Rukayadi; Yana Maolana Syah; Tri Cahyanto (Syarif Hidayatullah State Islamic University, 2022)
In this study, two lignan compounds were isolated from acetone extract of Phyllanthus niruri L. nirtetralin B (1) and phyllanthin (2) using several chromatographic methods followed by molecular structure elucidation mainly based on 1D and 2D of 1H and 13C NMR spectrum. The isolated compounds were tested for their antimicrobial properties against the plant pathogenic fungus, Fusarium oxysporum, using the agar plate well diffusion method. The microdilution method determined the minimum inhibitory concentration (MIC) and the minimum fungicide concentration (MFC). In addition, the microconidia germination inhibition test was carried out using the agar diffusion method. As a result, compound 1 had MIC and MFC values of 4 and 16 μg/mL, respectively. While compound 2 showed the same MIC and MFC values of 16 μg/mL. Further testing on the inhibition of germination of F. oxysporum microconidia showed that compound 2 inhibited microconidia germination 100% at a concentration of 2 × MIC. In comparison, compound 1 at the same concentration was only able to inhibit germination by 29%. This study revealed that compound 2 is a potential new fungicide derived from local medicinal plants. However, further research is needed to identify the interaction mechanism between the test compound and the fungal pathogen F. oxysporum to develop new antifungal agents.